Gender Influences On Psychopathology And Functionality In Schizophrenia In University Malaya Medical Centre, Kuala Lumpur, Malaysia - Zuraida, N.Z.; Gill, J.S.; Koh, O.H.; Kanagasundram, S.; Saniah, A.R.; Sapini, Y.; Salina, M.; Zuraida, A. (2009)
Numerous studies on gender differences in schizophrenia have been published to summarize the evidence from molecular to the clinical level. Female schizophrenics are found to have better skills then the males. In addition, it was described that the male schizophrenics exhibited more negative symptoms compared to the females. The aim of this study was to investigate the gender influences on psychopathology and functionality of schizophrenia patie nts in University Malaya Medical Centre. Methods: All patients diagnosed with schizophrenia who attended the outpatient psychiatric clinic during a two-month period were recruited into the study.The patients were assessed on their socio-demographic profile, clinical data, psychopathology according to Positive and Negative Syndrome Scale for Schizophrenia (PANSS) and functionality by using Personal and Social Performance Scale (PSP). Results: A total of 76 female and 74 male patients entered the study. Both genders were matched in age, ethnic groups, educational background and duration of illness. There were more singles among the male schizophrenics. 72% of the female schizophrenics and 87% of the males were on atypical antipsychotics (p<0.05). 57% of the female and 55% of the male schizophrenics hold a job. There were no significant differences in positive, negative and general psychopathology in both genders. The mean total score of PANSS was 46.5 in the females and 48.2 in the males. There was also no significant difference of PSP total score in both gender. The mean score of PSP was 73.0 for female schizophrenics and 70.0 for the males. PANSS scores was negatively correlated with PSP scores (r = - 0.70, p<0.001). Conclusion: There were no gender differences in psychopathology and functionality among schizophrenia patients attending psychiatric outpatient clinic in University Malaya Medical Center. Both genders are functioning well and more than half are having a job.